2015
DOI: 10.4293/jsls.2015.00040
|View full text |Cite
|
Sign up to set email alerts
|

Staple Line Reinforcement Methods in Laparoscopic Sleeve Gastrectomy: Comparison of Burst Pressures and Leaks

Abstract: Background and Objectives:Laparoscopic sleeve gastrectomy is a technically simple and popular bariatric operation with acceptable results. However, leaks can occur in long staple lines, for which various reinforcement methods are used. We compared nonreinforced stapling in laparoscopic sleeve gastrectomy with 3 staple line reinforcement methods: suturing, absorbable buttressing material, and fibrin glue.Methods:From March 1 until September 30, 2014, 118 patients with body mass index >40 kg/m2 underwent sleeve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Suturing afforded the highest burst pressure (mean pressure 74.9 mmHg) and took the longest to perform among the methods but there was no correlation between the leaks and burst pressures. All leaks in the patients were detected in the proximal stomach within 5 cm of the GE junction [41]. In our opinion, the most important bias was the evaluation of burst pressure in the resected stomach which is a structure too much different from the sleeve.…”
Section: Reinforcementmentioning
confidence: 98%
See 1 more Smart Citation
“…Suturing afforded the highest burst pressure (mean pressure 74.9 mmHg) and took the longest to perform among the methods but there was no correlation between the leaks and burst pressures. All leaks in the patients were detected in the proximal stomach within 5 cm of the GE junction [41]. In our opinion, the most important bias was the evaluation of burst pressure in the resected stomach which is a structure too much different from the sleeve.…”
Section: Reinforcementmentioning
confidence: 98%
“…A recent study published by Aydin et al [41] evaluates the burst pressures of the resected stomach specimens and adverse postoperative events. The authors divided the measurements based on the preferred type of staple line reinforcement; group I: 25 patients, no reinforcement (NoR); group II: 26 patients, fibrin glue (FG) (Tissell; Baxter International, Deerfield, Illinois); group III: 44 patients, suture reinforcement with 2-0 polypropylene sutures (S); and group IV: 14 patients, the biological buttressing material Peri-Strip Dry (PS) (Baxter International).…”
Section: Reinforcementmentioning
confidence: 99%
“…Several strategies, including the use of glue, have been used to prevent and decrease complications and also to manage them when they occur. [11][12][13][14] This observational comparative study suggests that using surgical glue during LSG is associated with a reduced duration of operation and a reduced inpatient total cost. The average cost to avoid a severe complication with the glue is significantly negative.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, similar results were reported by Timucin Aydin et al; they showed the highest burst pressure in the oversewed resected stomach. 12 However, they used the whole resected stomach, with the fundus, whereas in the present study, the gastric specimen was resected a second time to achieve a similar diameter of the LSG. We could speculate that the effects we found are promoted by the fact that the sero-serosal invagination creates a “chamber-like” above the whole staple line.…”
Section: Discussionmentioning
confidence: 99%